Integrated Power Domain NOMA and Orthogonal Multiple Access for Wireless Sensor Networks Based On High-Altitude Platform - MAHYASTUTYA Veronica Windha; PAMUKTI Brian; SARI Ratna (Journal of Electrical and Electronics Engineering)
This study examines an uplink system for a high-altitude platform (HAP) using a combination of orthogonal frequency division multiple access (OFDMA) and power domain non-orthogonal multiple access (PD-NOMA). We analyze how different HAP movements affect the system's bit error rate (BER). The findings reveal that OFDMA PD-NOMA efficiently allocates resources and prioritizes users within sub-channels. Vertical and horizontal HAP movement impacts the user signal-to-noise ratio (SNR), requiring values between 36.7 dB and 48 dB for a BER of 10 to (-3). The average SNR needed for the target BER is highest during vertical movement due to closer user proximity.